Music in Profile: Twelve Performance Studies - Rink, John (New York Oxford University Press, 2023)
"This book reflects the increasing significance of musical performance studies in recent decades. Originally published as separate essays over thirty years, the twelve chapters have been refashioned as a monograph which is both scholarly in nature and intensely personal, building on the author's extensive musical experience, most notably as a pianist. Hence the primary focus on piano music by Chopin, Schubert, Liszt, Brahms and Rachmaninoff. The book's cross-cutting themes nevertheless apply to diverse performance idioms and domains. By exploring themes in complementary ways, the book offers broad insights into musical ontology, epistemology and semantics while demonstrating various methodologies now used to study performance. Among other things, it highlights the powerful effects that experiencing music in performance can have on those who take part in it, in any capacity. There are many practical insights too. The volume has four sections, focusing on 'performance and performance studies', historical performance, analysis and performance, and artistic research. Case studies of romantic masterpieces for the piano feature throughout"--
Part 1. On performance and performance studies. The state of play in musical performance studies ; Impersonating the music in performance ; The work of the performer -- Part 2. On historical performance. Moments of truth : performing musicology ; Translating musical meaning : the performer as narrator ; Authentic Chopin -- Part 3. On analysis and performance. From analysis to 'performer's analysis' ; Playing in time ; Analysing motif and gesture in performance ; The (f)utility of performance analysis -- Part 4. On artistic research. Judging Chopin : an evaluation of musical experience ; Between practice and theory: performance studies and/as artistic research.
Includes bibliographical references and index.
Keywords: Chopin, Frédéric -- 1810-1849; Performance; Music philosophy and esthetics; Music history; Musical analysis